1975
DOI: 10.1152/ajplegacy.1975.228.3.850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of peptidase activity on distribution of intrarenal blood flow

Abstract: Experiments were performed in dogs to determine the effects of the intravenous administration of the dipeptide hydrolase inhibitor SQ 20,881 on renal hemodynamics, intrarenal blood flow distribution, and renal function. Dipeptide hydrolase converts angiotensin I to angiotensin II and inactivates bradykinin. SQ 20,881 causes an inhibition of the vasoconstrictor response after angiotensin I and potentiation of the vasodilatory activity of bradykinin. Total renal blood flow, cortical distribution of blood flow, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The vasodilatation seems to take place in the inner and middle cortical layer. In this respect we can confirm the findings of Bailie and Barbour [2] and Mimran et al [20]. Again, however, we would like to draw attention to possible methodologic artifacts in the results of intrarenal flow distribution.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The vasodilatation seems to take place in the inner and middle cortical layer. In this respect we can confirm the findings of Bailie and Barbour [2] and Mimran et al [20]. Again, however, we would like to draw attention to possible methodologic artifacts in the results of intrarenal flow distribution.…”
Section: Discussionsupporting
confidence: 88%
“…Cerebral frontal cortex (2), right ventricle (4), left ventricle (4), lung (2), liver (2), pancreas (3), spleen (3), stomach (2), jejunum (1), colon (1), adrenal (2), kidney (2), renal medulla (6), renal cortex divided in inner (6), middle (6), and outer layer (6), fat (2), skin (2) and muscle (6). A detailed description of the sampling procedure is given in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…During maximal postarrhythmic renal vasoconistrictioni (4 min) renal capsular catecholamines were threefold higher than femoral arterial levels. Comparison of changes in femoral arterial catecholamine levels in these six dogs in response to atrial fibrillation revealed no significanit difference from those seen in the nine animals reported in Table II. The changes from preintervention control hemodvnamics to control hemodynamiiics during an intervention (SQ 20881, phentolamine, propranolol, vagal cooling, atropine renal denervation, bretylium, and hexamethonium) were the same as have been previously reported in the pentobarbital-anesthetized dog and will not be discussed further unless appropriate to the focus of this study (10)(11)(12)(13)(14). tribution of blood flow have been observed in response his study caused a dis-to exercise in the conscious dog with complete heart ion of renal blood flow block (15).…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, dissociation between sodium excretion and GFR under circumstances of increased and decreased All levels might suggest the involvement of an additional factor, possibly activation of the kallikreinkinin system. 22 In RHT dogs, both All and CEI caused significant natriuresis apparently resulting from different effects on the renal circulation. While in hypertensive animals a decrease in pre-and postglomerular resistance appears to be the most likely cause for the sodium diuresis produced by CEI, an increase in postglomerular capillary pressure may account for the results obtained with infusion of angiotensin II.…”
Section: Figure 4 Comparison Of Percent Changes In Urinary Sodium Exmentioning
confidence: 99%